Dimens\~oes da abordagem da cadeia global de valor: Upgrading, governança, políticas governamentais e propriedade intelectual - Eduardo Costa Pinto; Ronaldo Fiani; Ludmila Macedo Corrêa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper aims to i) to present the main dimensions of the Global Value Chain approach (upgrading, governance and government policies); and ii) to investigate the impacts of intellectual property protection on the upgrading possibilities of developing countries by means of presenting of the main aspects of Trips (Agreement on Trade-Related Aspects of Intellectual) and its impacts.
Keywords: F10; F13; 330; global value chains; intellectual property; international trade; public policies